The effect of the alcohol content in the fuel mixture on the performance and emissions of a direct injection diesel engine fueled with diesel-methanol and diesel-ethanol blends. (15th September 2017) - Jamrozik, Arkadiusz
Highlights: Co-combustion of diesel fuel with methanol and ethanol. Combustion phases are shifted after the addition of alcohol to diesel fuel. Diesel-methanol and diesel-ethanol blends show an increase in thermal efficiency. Addition of alcohol leads to an increase in NOx emission. Abstract: The study presents experimental examinations of a single-cylinder stationary diesel engine fueled with diesel-methanol and diesel-ethanol blends. Volume percent of alcohol in the blends ranged from 0 to 40%. The addition and the increase in the methanol content of up to 30% in diesel-methanol blends had a positive effect on thermal efficiency of the engine whereas no significant changes were found in the values of indicated mean effective pressure. Moreover this increase led to a substantial reduction in carbon monoxide emissions and did show a significant effect on emissions of hydrocarbons and carbon dioxide. Further increase in volume percent of methanol of over 30% caused disturbances in the combustion process, a substantial decline in in-cylinder pressure and unsteady engine work. In the case of the diesel-ethanol blends, the improved work of the test engine was observed for all alcohol content values. Engine efficiency increased while maintaining the constant level of indicated mean effective pressure. CO emissions were reduced, whereas THC and CO2 emissions remained virtually unchanged. Addition of alcohol had a negative effect on nitrogen oxides emissions from the engine fueled with both diesel-methanol and diesel-ethanol blends. After exceeding the 30% content of alcohol, the work non-repeatability reflected by the COVIMEP coefficient increased to over 10%, which can be considered as a limit of steady work of the combustion engine.